CIOs at work - Yourdon, Edward (Apress ; Distributed to the Book trade by Springer, 2011)
Presents interviews with the chief information officers of various corporations, as they discuss their role in corporate culture, their choices of technologies that improve productivity, and their assessment of the technologies of the future.